FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN BAYI BERAT LAHIR RENDAH PADA IBU HAMIL DI POLI KEBIDANAN RUMAH SAKIT IBU DAN ANAK PEMERINTAH ACEH - Iftahuddin Iftahuddin; Julinar Julinar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
The prevalence of low birth weight in Indonesia is actually a detrimental case. In 2017 alone, the prevalence of low birth weight increased by 1.5 %compared to the previous year. Low birth weight becomes the second highest causeof mortality in Aceh with the percentage of 21% while the highest cause of babies mortality is perinatal disorders. Low birth weight is six times more risky on babies mortality compared to normal birth weight. The LBW is triggered by some factors like genetic, demography, and delivery history. The aim of this research is to define the factors that influence LBW prevalence among women treated at the midwifery unit inIbu dan Anak Public Hospital of Aceh. The type of this research is quantitative. The research instrument is a questionnaire. The data were collected from July 10 to July 13, 2018. The total population of this research is 98 respondents with the sample of 31 respondents. The sampling technique used in this research is proportional sampling. The result shows that the genetic factor influences the LBW to 19 respondents (61.3%), while the demographic factor influences the LBW to 20 respondents (64.5%). Moreover, the delivery history influences the LBW to 18 respondents (58.1%). It can be concluded that generally that all factors mentioned recently influence the LBW prevalence among women treated at the unit of midwifery in the Ibu dan Anak Public Hospital of Aceh. It is suggested that the medical workers to improve their understanding of pregnant women in relation to the LBW influencing factors, so they can have a good coping mechanism in facing the delivery of babies with LBW.Keywords: Pregnant mother, Low Birth Weight (LBW) prevalence